Awareness and hesitancy of COVID-19 and other vaccines among people living with HIV/AIDS attending antiretroviral therapy (ART) center in North India - Aman Dev Singh; Naina Upal; Simmi Oberoi; Namrata Singh; Archit Garg; Avneet Kaur; Ashujot Kaur (Wolters Kluwer Medknow Publications, 2023)
Introduction: Approximately 40 years have passed since we first learned about the human immunodeficiency virus (HIV), but several people living with HIV (PLHIV) in developing countries such as India cannot avail treatments. This makes preventive measures, such as vaccinations, critical in these persons to avoid vaccine preventable diseases (VPDs). However, little is known about the willingness and perceptions of PLHIV regarding these vaccines. Therefore, we explored vaccine awareness and hesitancy, especially during the recent COVID-19 pandemic. Objectives: The primary objective was to determine the uptake of the Covid-19 vaccine and other VPD's among PLHIV and factors affecting the same in Antiretroviral therapy (ART) centers in a tertiary care hospital in North India. Research Design and Methods: This was a cross-sectional study of HIV patients who attended our Antiretroviral Therapy center (ART). Clinical data were collected using a questionnaire on general profile, disease information, knowledge, attitude, and practice (KAP) regarding vaccinations, and vaccination status for different VPDs. Results/Findings: We enrolled 300 subjects and found that 82% of the patients attending our ART center were aware of vaccinations, most of whom were aware of the polio vaccine (n=91, 30.33%), followed by tuberculosis (n=61, 20.33%), and the majority of them were not aware of vaccines indicated in PLHIV. We also found that the majority (n= 240, 80.23%) of patients had vaccine hesitancy, especially regarding the new COVID-19 vaccine. Conclusion: There is a need to create awareness among people about the benefits and uses of vaccination to achieve the greater goal of reduced morbidity and mortality among PLHIV. There is a need for free vaccination programs for VPDs in PLHIV patients.